Clinical and molecular genetic findings of Crisponi/cold‐induced sweating syndrome (CS/CISS) spectrum in patients from Turkey. Issue 3 (12th July 2022) - Yilmaz Gulec, Elif; Turgut, Gozde Tutku; Gezdirici, Alper; Karaman, Volkan; Ozturk, Fatma Nihal; Avci, Sahin; Kalayci, Tugba; Senturk, Leyli; Ayaz, Akif; Kayserili, Hulya; Uyguner, Zehra Oya; Altunoğlu, Umut
Abstract: Crisponi/cold‐induced sweating syndrome (CS/CISS) is a rare autosomal recessive disorder characterized by episodic hyperthermia, arthrogryposis, impaired feeding ability, and respiratory distress. The classic CS/CISS is mainly associated with CRLF1 and, rarely, CLCF1 . PERCHING syndrome, previously known as CS/CISS type‐3 associated with biallelic pathogenic variants in KLHL7, is notable for its few overlapping manifestations. This study presents genotype–phenotype relationships in CS/CISS‐like spectrum associated with CRLF1 and KLHL7 . Clinical findings of 19 patients from 14 families and four patients from three families were found in association with six different CRLF1 and three different KLHL7 variants, respectively. c.167T>C and c.713delC of the CRLF1 gene and the c.642G>C of the KLHL7 were novel. The c.708_709delCCinsT allele of CRLF1 was identified in 10 families from the Mardin province of Turkey, underlining that an ancestral haplotype has become widespread. CRLF1 ‐associated phenotypes revealed novel manifestations such as prenatal oligohydramnios, benign external hydrocephalus, previously unreported dysmorphic features emerging with advancing age, severe palmoplantar keratoderma and facial erythema, hypopigmented macules and streaks, and recurrent cardiac arrests. KLHL7 variants presented with glabellar nevus flammeus, blepharophimosis, microcephaly, thin corpus callosum, and cleft palate. Abnormalities of sweating, observed in one patient reported herein, is known to be very rare among KLHL7 ‐related phenotypes. Abstract :